Complaint as an Act: (Complaint Analysis in Twilight Novel) - Hetty Catur Ellyawati (Surakarta English and Literature Journal, 2018)
Complaint as a communicative act can be divided into two categories. First, as a face threatening act when it is uttered directly, second, it becomes a politeness when it uses indirectness. This research is explanatory research which tries to explain why complaint can have many different strategies. For data collection, the writer used purposive sampling taken from Twilight novel written by Stephani Meyer, but the writer chose Bahasa Indonesia version. While for analyzing the data, the writer used substitution method with social context consideration. From the data analysis, it is found that complaint is always a face threatening act when it is used directly.